The Values of Character Education in Digital Da'wah: Analyzing Gus Iqdam’s TikTok Content and Its Impact - Taufikin, Taufikin; Falah, Ahmad (Southeast Asian Journal of Islamic Education, 2025)
This study investigates how character education values are communicated and internalized through digital Islamic preaching on TikTok, focusing on the sermons of Gus Iqdam, an influential Indonesian preacher whose content resonates with millions of young followers. While his videos are widely consumed and celebrated for their humor and relatability, many audience members engage with the content passively, without translating the moral messages into real-life behavior. This research aims to explore the core character values conveyed in his digital sermons and assess their impact on audience comprehension and behavioral change. Employing a qualitative case study design, data were collected through systematic content observation of selected TikTok sermons, semi-structured interviews with 50 active followers, and content analysis of the values embedded in the sermons. The findings reveal that Gus Iqdam promotes key moral values such as honesty, patience, empathy, respect, and responsibility through storytelling, humor, and everyday analogies. His casual language and culturally grounded delivery style serve as a bridge that connects moral lessons with the lived realities of young audiences. Interview data indicate that many followers felt personally influenced to reflect and act upon these values, although not all engagement led to transformation. This study contributes to a deeper understanding of how digital religious content can function as a medium of informal moral education, offering valuable insights for educators, preachers, and digital content creators aiming to reach and impact today’s digital-native generation.